Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.jmbbm.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Indirect 3D bioprinting and characterization of alginate scaffolds for potential nerve tissue engineering applications

Abstract: Saman Naghieh) and xbc719@mail.usask.ca (Xiongbiao Chen). AbstractLow-concentration hydrogels have favorable properties for many cell functions in tissue engineering but are considerably limited from a scaffold fabrication point of view due to poor three-dimensional (3D) printability. Here, we developed an indirect-bioprinting process for alginate scaffolds and characterized the potential of these scaffolds for nerve tissue engineering applications. The indirect-bioprinting process involves (1) printing a sacr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 43 publications
0
44
0
Order By: Relevance
“…The pure alginate samples (Group 1), Group G, Group 3, and Group 4 showed 32.53%, 13.33%, 40.00%, and 19.70% degradation, respectively, over time incubated in PBS. PBS has been used widely to evaluate the degradation rate of scaffolds, as reported in References [11,[28][29][30]. Notably, as future work, other solutions such as fetal bovine serum and penicillin-streptomycin contained medium can be used to check the degradation rate of scaffolds.…”
Section: Swelling Properties Degradation and Mechanical Characterizmentioning
confidence: 99%
See 1 more Smart Citation
“…The pure alginate samples (Group 1), Group G, Group 3, and Group 4 showed 32.53%, 13.33%, 40.00%, and 19.70% degradation, respectively, over time incubated in PBS. PBS has been used widely to evaluate the degradation rate of scaffolds, as reported in References [11,[28][29][30]. Notably, as future work, other solutions such as fetal bovine serum and penicillin-streptomycin contained medium can be used to check the degradation rate of scaffolds.…”
Section: Swelling Properties Degradation and Mechanical Characterizmentioning
confidence: 99%
“…It means that factors affecting printability such as pressure can directly affect cell viability and that is why it is important to consider cell viability. Readers are encouraged to check a recent study on printability and cell viability for more information [29].…”
Section: Groupsmentioning
confidence: 99%
“…Compared with implanted collagen sponge and fibrin glue, nerve regeneration in alginate hydrogel is much better. Saman et al [73] used indirect 3D printing to prepare a sodium alginate hydrogel scaffold that embeds Schwann cells at the expense of gelatin frames. The results of the study showed that Schwann cells in this scaffold were more viable than those in bulk gel.…”
Section: Printable Hydrogelsmentioning
confidence: 99%
“…Scaffolds with living cells and/or bioactive molecules can be fabricated using 3D bioprinting techniques, where a scaffold is fabricated by laying down threads or fibers of bioink, i.e., the mixture of hydrogel, living cells, and/or bioactive molecules, in a controllable layer-by-layer manner [46]. Specifically, Chen et al have illustrated the feasibility of bioprinting scaffolds from alginate hydrogel or a composite hydrogel mixture of alginate and hyaluronic acid, with both controlled microstructure and controlled distribution of living Schwann cells for use in peripheral nerve repair applications [26,[47][48][49][50][51].…”
Section: D Bioprinted Bioactive Biomaterialsmentioning
confidence: 99%